(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
Agenda concerning terrorism, which is associated with transnational organized crime groups, are constantly expanding. Most of the activities that terrorist groups must participate in order to achieve their goals are criminal, while in some cases criminal activity is used strategically as part of the mechanism to finance terrorist organizations. Interaction between terrorism and transnational organized crime is becoming deeper and more complex. This paper identifies three main models of criminal / terrorist interface: Interaction - alliances to achieve mutual profit; discreet involvement of terrorist groups in organized crime by eliminating the middleman but maintaining the ideological conventions of their strategy and replacement of ideology with a profit as the main motive for action. In this paper, we analyse one part of the terrorist - criminal spectrum - the permanent / regular cooperation, sharing objectives and the formation of strategic alliances between terrorist groups and transnational criminal organizations.